2004
DOI: 10.1023/b:phot.0000040588.31318.0f
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Tolerance of Tobacco Plants Transformed to Accumulate Proline, Fructans, or Glycine Betaine. Variable Chlorophyll Fluorescence Evidence

Abstract: Tobacco (Nicotiana tabacum L.) has been transformed to accumulate different compatible solutes (proline, fructans, or glycine betaine) in order to improve its tolerance to abiotic stress. Photosynthetic activity of wild type (wt) and transformed tobacco plants before and after freezing stress was studied by measuring chlorophyll (Chl) fluorescence. The JIP test of Chl fluorescence induction was used to analyze in details the functional activity of photosystem 2. No significant differences were found among wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 33 publications
(33 reference statements)
1
24
0
Order By: Relevance
“…Chilling‐associated decreases in PSII function occur in many plants because of a multitude of possible perturbations including oxidative damage to thylakoids (Tambussi et al 2004), inhibition of electron transport by downstream regulation to match a lower ATP and NADPH demand during reductive carbon metabolism (Zhou et al 2004) and conformational changes/dissociation of PSII proteins (Higuchi et al 2003, Parvanova et al 2004). Bertamini et al (2006) recently demonstrated pronounced dark‐chilling‐induced degradation of the D1 RC protein in grapevine plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chilling‐associated decreases in PSII function occur in many plants because of a multitude of possible perturbations including oxidative damage to thylakoids (Tambussi et al 2004), inhibition of electron transport by downstream regulation to match a lower ATP and NADPH demand during reductive carbon metabolism (Zhou et al 2004) and conformational changes/dissociation of PSII proteins (Higuchi et al 2003, Parvanova et al 2004). Bertamini et al (2006) recently demonstrated pronounced dark‐chilling‐induced degradation of the D1 RC protein in grapevine plants.…”
Section: Discussionmentioning
confidence: 99%
“…Chilling-associated decreases in PSII function occur in many plants because of a multitude of possible perturbations including oxidative damage to thylakoids (Tambussi (Higuchi et al 2003, Parvanova et al 2004). Bertamini et al (2006) recently demonstrated pronounced dark-chilling-induced degradation of the D1 RC protein in grapevine plants.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic tobacco plants carrying SacB (Konstantinova et al 2002) and transgenic ryegrass plants carrying fructosyltransferase gene (Hisano et al 2004) showed increased cold tolerance under freezing stress conditions. Moreover, fructan could reduce the oxidative stress (Parvanova et al 2004a) and photo-inhibition (Parvanova et al 2004b) caused by low temperature. Thorsteinsson et al (2002) found that 1-kestose was the only low degree polymers (DP) fructan (<12) significantly accumulated in response to the low temperature in two cultivars of timothy (Phleum pretense).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the concept 'sugar as antioxidant' has been put forward in recent years [56], and some genes encoding different sugar compounds were con rmed to enhance low temperature tolerance in petunia, tobacco and rice [57][58][59][60][61]. It is more and more recognized that water-soluble carbohydrates (glucose, fructose and sucrose) are regarded as key regulators in plant responses to abiotic/biotic stress.…”
Section: Sugar As Antioxidants In Sweetpotato Rootsmentioning
confidence: 99%